Basic anatomy, physiology and pathophysiology of the cerebral circulation for the physician - Baron, Jean-Claude (Henry Stewart Talks, 2008)
Anatomy of the cerebral arteries and veins, Main arterial territories, Physiological regulation of cerebral blood flow, Autoregulation of cerebral blood flow in physiological and pathological conditions, The four stages of haemodynamic impairment in cerebrovascular occlusive disease, Reperfusion of the ischaemic brain
Reviewed at 2022/04/12